Synchronous Responses of Plant Functional Traits to Nitrogen Deposition From Dominant Species to Functional Groups and Whole Communities in Alpine Grasslands on the Qinghai-Tibetan Plateau - Li, Shuai; Zhao, Zhenzhen; Dong, Shikui; Shen, Hao; Xu, Yudan; Xiao, Jiannan; Gao, Xiaoxia; Wu, Shengnan; Stufkens, Paul (Frontiers in Plant Science, 2022)
Nitrogen deposition is recognized as one of the major threats to the ecosystem function of alpine grasslands on the Qinghai-Tibetan Plateau (QTP). However, few studies have documented the gradient responses of plant species, functional groups, and communities in alpine grassland ecosystems to various levels of N deposition on the QTP. We applied eight linear mixed-effect models combing acidification, eutrophication, and phosphorus availability to explore if the responses of plant functional traits (particularly plant height and specific leaf area) from dominant species to functional groups and whole communities in different types of grassland to nitrogen deposition were consistent with the same or different models. We found that the specific leaf area of Stipa capillata, non-forb, and community weighted mean value in the alpine steppe were synchronous and related to acidification with nitrogen addition; the height of Stipa capillata, non-forb, and community weighted mean value in the alpine steppe was synchronous and related to acidification, eutrophication and phosphorus availability with nitrogen addition; the height and specific leaf area of Elymus breviaristatus to functional groups and community weighted mean value in cultivated grasslands were synchronous and related to acidification, eutrophication and phosphorus availability with nitrogen addition. Most of the responses of plant functional traits to acidification, eutrophication, and phosphorus availability associated with nitrogen deposition in the alpine steppe and the cultivated grassland were synchronous, while only the response of the specific leaf area of forb functional groups to eutrophication associated with N deposition in the alpine steppe was asynchronous.